If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12c + -4 = -12c Reorder the terms: -4 + 12c = -12c Solving -4 + 12c = -12c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '12c' to each side of the equation. -4 + 12c + 12c = -12c + 12c Combine like terms: 12c + 12c = 24c -4 + 24c = -12c + 12c Combine like terms: -12c + 12c = 0 -4 + 24c = 0 Add '4' to each side of the equation. -4 + 4 + 24c = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 24c = 0 + 4 24c = 0 + 4 Combine like terms: 0 + 4 = 4 24c = 4 Divide each side by '24'. c = 0.1666666667 Simplifying c = 0.1666666667
| 12-5x=6(x+2) | | 3.4k=7.82 | | 2q-5=11 | | 225x^2-121y^2= | | 7+-3=18 | | 1-100x^2= | | (2c-1)=3c-2 | | 10+5(z-2)=-3z+3 | | 2x^3+3x^2-120=f(x) | | 3/4*3/4= | | -52=5x-4(-x-5) | | 2x^3+3x^2-120=0 | | 10-6x-3=1 | | 24(x+3)=0 | | 28-z=5 | | 2+14a=20a-5a | | z*z-(2+1i)z+(-1+7i)=0 | | -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) | | -5x=2x | | x^2-12x=8064 | | 8(5k-3)=-264 | | x^2-12x=5440 | | 9(y+5)=8y-6 | | 125*.38= |